Analysis of the Potential of the Sport Branch of Paraplaying in the Development of Sport Tourism in Lahat District - Apriansyah, Weter; Handayani, Widya; Rizhardi, Rury (PPSDP International Journal of Education, 2024)
This research aims to analyze the potential of the paragliding sport to be developed into sport tourism in Lahat district. This research is qualitative research. Data for this analysis was collected through interviews with the head of tourism and the chairman of the PASI (Indonesian Aero Sport Management) board, as well as direct observation at the paragliding training site. In addition, secondary data from visit reports at tourism sites is used to support this analysis. The results of the analysis showed that the strengths are the beautiful views of Lahat Regency, especially at Juko Kayu Kambing Hill, Kota Agung District. Weaknesses, identified include limited road access to the paragliding venue. Opportunities, for the paragliding team include the potential for tourism development, increasing the popularity of paragliding at the regional level, and the possibility of getting investors both locally and internationally. This research describes strategies to increase the potential for sports tourism development, such as improving road access and tourism facilities as well as sponsor support. By implementing this strategy, it is hoped that sport tourism will develop in the paragliding sport in Lahat Regency, South Sumatra, and become a tourism destination.